Model-Based Re-Examination of the Effectiveness of Tumor/Immunohistochemistry and Direct-to-Sequencing Protocols for Lynch Syndrome Case Finding in Endometrial Cancer. Issue 11 (November 2021) - Gudgeon, James M.; Varner, Michael W.; Hao, Jing; Williams, Marc S.
Abstract : PURPOSE: Despite widespread provision of Lynch syndrome (LS) screening programs, questions remain about the most effective and efficient protocol for LS case finding. The purpose of this study was to explore the performance of the two protocols widely shown to be the most efficient and effective, respectively: immunohistochemical (IHC) staining of tumor and direct-to-sequencing (DtS) in endometrial cancer populations. METHODS: Simulation models were developed to explore performance of the IHC and DtS protocols, updated to reflect current evidence. Analyses explicitly account for protocol complexity and failure points, as well as decreased sequencing costs. Key outcomes are percent of LS cases identified, total protocol costs and efficiency, and break-even analyses of sequencing costs. All costs are in 2020 US dollars (USD). RESULTS: Under plausible conditions, the IHC protocol is expected to identify 40%-78% of LS cases and DtS protocol from 49% to 97%. When the key variable success in proceeding to sequencing is fixed for both protocols at 50%, 75%, and 100%, the DtS protocol is 9%, 12%, and 16% better at case finding, respectively, than the IHC protocol. The break-even cost of sequencing is about $488 USD when the outcome is total direct testing protocol costs; it is about $670 USD when the outcome is cost per LS case detected. CONCLUSION: This study quantifies the plausible differences in the clinical effectiveness and cost-effectiveness of the two LS case-finding protocols. We demonstrate the large influence of success in proceeding to sequencing and potential impact of decreasing sequencing prices.